Effect of endosulfan on blood gases in the edible fish Oreochromis mossambicus (Peters) - Rangaswamy, C P (Indian Journal of Fisheries, 2011)
Oxygen capacity, oxygen and carbon dioxide contents of blood of control O. mossambicus were 14.33, 4.06 and 8.01 vol. % respectively. Upon exposure to sublethal and lethal concentrations of endosulfan, the oxygen content of blood decreased, while the carbon dioxide content increased. Blood pH decreased due to increase in its C02 content. Derangement in blood gas levels under endosulfan toxicity signifies inability of the pigment to carry out its normal respiratory functions. This calls for careful application of pesticides to protect inland water life including fish.